How acceptable are the prevention of mother to child transmission (PMTCT) of HIV services among pregnant women in a secondary health facility in Ibadan, Nigeria? (2015)
Background: Prevention of mother to child transmission of HIV (PMTCT) programme was designed to reduce mother to child transmission (MTCT) of HIV and it has been shown to be effective. However, the uptake of the services is still very low in Nigeria. Objective : This study was designed to determine how acceptable the different services of PMTCT are to pregnant women in Ibadan, Nigeria. Method : Systematic random sampling was used to recruit 500 pregnant women attending antenatal clinic in a secondary health facility. Questionnaires were used to obtain data regarding socio-demographic characteristics, knowledge about MTCT of HIV and prevention, the awareness and attitude towards infant feeding options for HIV positive mothers. Data were analysed using student’s t test and Chi-square test with p set at 0.05. Results: Mean age of respondents was 27.4±6.1years. Most known routes of MTCT of HIV were during pregnancy (86.0%) and from breastfeeding (86.0%). More than 80% knew that having good antenatal care, appropriate supervised delivery, taking antiretroviral drugs and not breast feeding a baby are ways of PMTCT. About two thirds had a positive attitude towards HIV testing and counseling (HTC). Only 18.4% were aware of the exclusive breast feeding option for feeding infants of HIV positive mothers while 52.2% would not comply if asked not to breast feed. Women aged 35 years and above had better attitude towards non breast feeding. Conclusion : Intensified health education on the importance of HTC and promotion of exclusive breast feeding for infants of HIV positive mothers is recommended.